change yrds to ft
5yds = 5*3 = 15 ft
5yds 2 ft = 15ft + 2ft = 17 ft
6yds = 6 * 3 = 18 ft
6 yds 1 ft = 18 + 1
19 ft
A = l * w
A = 17* 19
A = 323 ft^2
Choice A
Answer:
508.68 or 508.7
Step-by-step explanation:
V=1/3(3.14)(9)^2(6)
(3.14)(81) x 6
(3.14)(486)
1/3(1526)
(divide by 3)= 508.68
Answer:
No graph so we'll use the quadratic formula
x^2+x-4=0
a = 1
b = 1
c = -4
x = -1 +- sqr root (1^2 - 4 * 1 * -4) / 2
x = (-1 +- sqr root (1 +16) ) / 2
x1 = (-1 + sqr root (17)) / 2
x2 = (-1 - sqr root (17)) / 2
Step-by-step explanation: